Dermoscopy of nevi and melanoma in childhood. (February 2011) - Brooks, Christine; Scope, Alon; Braun, Ralph P; Marghoob, Ashfaq A
Dermoscopy is a noninvasive technique that allows for the visualization of subsurface colors and structures within pigmented melanocytic skin lesions that are otherwise imperceptible to the naked eye. Dermoscopic findings have been formulated into diagnostic criteria that assist experienced clinicians in differentiating benign and malignant neoplasms. In essence, dermoscopy can help identify cutaneous malignancies, while at the same time minimizing the frequency of unwarranted biopsies of benign cutaneous lesions. In this article, we examine the clinical morphology of melanocytic nevi and melanoma in the pediatric population, and describe the relevant dermoscopic findings and histopathologic correlates that aid in the diagnosis and management of these lesions.